Brittle diabetes: psychopathological aspects - Pelizza, Lorenzo; Bonazzi, Federica; Scaltriti, Sara; Milli, Bruna; Giuseppina, Chierici (Acta Biomedica Atenei Parmensis, 2014)
Background. The term “brittle” is used to described an uncommon subgroup of type I diabetics whose lives are disrupted by severe glycaemic instability with repeated and prolonged hospitalization. Psychosocial problems are the major perceived underlying causes of brittle behaviour. Aim of this study is a systematic psychopathological assessement of brittleness using specific parameters of general psychopathology and personality traits following the multiaxial format (axis I and II) of the current DSM-IV-TR diagnostic criteria for mental disorders. Methods. Patients comprised 21 brittle type I diabetics and a case-control group of 21 stable diabetics, matched for age, gender, years of education, and diabetes duration. General psychopathology and the DSM-IV-TR personality traits/disorders were assessed using the Syptom Checklist-90-R (SCL-90-R) and the Millon Clinical Multiaxial Inventory-III (MCMI-III). Results. The comparison for SCL-90-R parameters exclusively revealed higher scores in “Phobic Anxiety” subscale in brittle diabetics. No differences in all the other SCL-90-R primary symptom dimensions and in the three SCL-90-R global distress indices were observed between the two diabetic groups, as well as in the all MCMI-III clinical syndrome categories corresponding to DSM-IV-TR specific psychiatric disorders. However, brittle patients presented lower scores in MCMI-III compulsive personality traits and higher scores in paranoid, schizoid, schizotypal, antisocial, borderline, narcissistic, avoidant, dependent, depressive, and passive-aggressive personality traits. Conclusions. In this study, brittle diabetics show no differencies in terms of global severity of psychopathological distress and axis I specific DSM-IV-TR diagnoses in comparison with non-brittle subjects (except for phobic anxiety). Differently, brittle diabetics are characterized from less functional and maladaptive personality features and suffer more frequently and intensively from specific pathological personality traits of all DSM-IV-TR clusters.